Transgenic zebrafish model of DUX4 misexpression reveals a developmental role in FSHD pathogenesis. (10th October 2018) - Pakula, Anna; Lek, Angela; Widrick, Jeffrey; Mitsuhashi, Hiroaki; Bugda Gwilt, Katlynn M; Gupta, Vandana A; Rahimov, Fedik; Criscione, June; Zhang, Yuanfan; Gibbs, Devin; Murphy, Quinn; Manglik, Anusha; et al.
Abstract: Facioscapulohumeral dystrophy type 1 (FSHD-1) is the most common autosomal dominant form of muscular dystrophy with a prevalence of ∼1 in 8000 individuals. It is considered a late-onset form of muscular dystrophy and leads to asymmetric muscle weakness in the facial, scapular, trunk and lower extremities. The prevalent hypothesis on disease pathogenesis is explained by misexpression of a germ line, primate-specific transcription factor DUX4-fl (double homeobox 4, full-length isoform) linked to the chromosome 4q35. In vitro and in vivo studies have demonstrated that very low levels of DUX4-fl expression are sufficient to induce an apoptotic and/or lethal phenotype, and therefore modeling of the disease has proved challenging. In this study, we expand upon our previously established injection model of DUX4 misexpression in zebrafish and describe a DUX4-inducible transgenic zebrafish model that better recapitulates the expression pattern and late onset phenotype characteristic of FSHD patients. We show that an induced burst of DUX4 expression during early development results in the onset of FSHD-like phenotypes in adulthood, even when DUX4 is no longer detectable. We also utilize our injection model to study long-term consequences of DUX4 expression in those that fail to show a developmental phenotype. Herein, we introduce a hypothesis that DUX4 expression during developmental stages is sufficient to induce FSHD-like phenotypes in later adulthood. Our findings point to a developmental role of DUX4 misexpression in the pathogenesis of FSHD and should be factored into the design of future therapies.